Recent Advances in Learning and Control - Blondel, Vincent D.; Boyd, Stephen P.; Kimura, Hidenori (Lecture Notes in Control and Information Sciences,, 2008)
This volume is composed of invited papers on learning and control. The contents form the proceedings of a workshop held in January 2008, in Hyderabad, that honoured the 60th birthday of Doctor Mathukumalli Vidyasagar. The 14 papers, written by international specialists in the field, cover a variety of interests within the broader field of learning and control. The editors have grouped these into the following 3 categories: learning and computational issues, learing for communication and identification, applications of learning and control. The diversity of the research presented gives the reader a unique opportunity to explore a comprehensive overview of a field of great interest to control and system theorists. The reader will benefit from the expert participants' ideas on the exciting new approaches to control and system theory and their predictions of future directions for the subject that were discussed at the workshop.